Gender‐Related Changes of the Epicardial Fat Thickness and Leptin in Obstructive Sleep Apnea. Issue 4 (16th October 2013) - Akilli, Hakan; Kayrak, Mehmet; Bekci, Taha Tahir; Erdogan, Halil İbrahim; Aribas, Alpay; Yildirim, Oguzhan; Taner, Alpaslan; Erer, Murat; Unlu, Ali
<x xml:space="preserve">Abstract</x> Background Epicardial fat thickness (EFT), an indicator of visceral obesity, and leptin are 2 novel markers for studying the obstructive sleep apnea (OSA) population. This study aimed to investigate the effects of gender on leptin levels and EFT, and the relation with OSA severity. Methods A total of 149 patients with OSA (female/male 55/94 and mean age 50.8 ± 9.2 years) and 50 control patients (female/male 24/26 and mean age 48.9 ± 8.8 years) were included in the study. The study population was divided into 4 groups according to apnea/hypopnea index (AHI) as control (AHI <5), the mild OSA (AHI 5–14), the moderate OSA (AHI 15–29), and the severe OSA (AHI ≥30). EFT was obtained from parasternal long‐axis and parasternal short‐axis echocardiographic images. Results Leptin levels among females were significantly higher than among males (10.5 [7.8] vs. 5.4 [4.5] ng/mL, P = 0.001, respectively). Among women, leptin levels were significantly higher in the severe OSA group compared to the control group (9.8 [9.0] vs. 15.5 [10.1] ng/mL, P = 0.05, respectively). Conversely, no relation was observed between OSA severity and the leptin levels among men. EFT was not significantly different between the 2 genders (P > 0.05). EFT was thicker in the severe OSA group than in the control and mild OSA groups among women, whereas EFT was not changed according to OSA severity among males (P > 0.05). Conclusion Leptin and EFT may be a valuable parameter in the evaluation of OSA severity in women than in men.